Fecal glucocorticoids and gastrointestinal parasite infections in wild western lowland gorillas (Gorilla gorilla gorilla) involved in ecotourism - Shutt-Phillips, Kathryn; Pafčo, Barbora; Heistermann, Michael; Kasim, Adetayo; Petrželková, Klára J; Profousová-Pšenková, Ilona; Modrý, David; Todd, Angelique; Fuh, Terence; Dicky, Jean-Francais; Bopalanzognako, Jean-Bruno; Setchell, Joanna M (General and comparative endocrinology, 2021)
Wildlife ecotourism can offer a source of revenue which benefits local development and conservation simultaneously. However, habituation of wildlife for ecotourism can cause long-term elevation of glucocorticoid hormones, which may suppress immune function and increase an animal's vulnerability to disease. We have previously shown that western lowland gorillas (Gorilla gorilla gorilla) undergoing habituation in Dzanga-Sangha Protected Areas, Central African Republic, have higher fecal glucocorticoid metabolite (FGCM) levels than both habituated and unhabituated gorillas. Here, we tested the relationship between FGCM levels and strongylid infections in the same gorillas. If high FGCM levels suppress the immune system, we predicted that FGCM levels will be positively associated with strongylid egg counts and that gorillas undergoing habituation will have the highest strongylid egg counts, relative to both habituated and unhabituated gorillas. We collected fecal samples over 12 months in two habituated gorilla groups, one group undergoing habituation and completely unhabituated gorillas. We established FGCM levels and fecal egg counts of Necator/Oesophagostomum spp. and Mammomonogamus sp. Controlling for seasonal variation and age-sex category in strongylid infections we found no significant relationship between FGCMs and Nectator/Oesophagostomum spp. or Mammomonogamus sp. egg counts in a within group comparison in either a habituated group or a group undergoing habituation. However, across groups, egg counts of Nectator/Oesophagostomum spp. were lowest in unhabituated animals and highest in the group undergoing habituation, matching the differences in FGCM levels among these gorilla groups. Our findings partially support the hypothesis that elevated glucocorticoids reduce a host's ability to control the extent of parasitic infections, and show the importance of non-invasive monitoring of endocrine function and parasite infection in individuals exposed to human pressure including habituation process and ecotourism.
Keywords: Parasites; Animals; Ape Diseases; parazitární nemoci; Parasitic Diseases; Gorilla gorilla; paraziti; zvířata; feces; Feces; glukokortikoidy; Glucocorticoids; nemoci lidoopů